Factors of attracting and resisting investment in the tourism industry in Algeria - Fattouch, Soumiya; Ouadah, Fouaz (Milev Journal of Research and Studies, 2018)
This study deals with the factors attracting investment in tourism and its constituents in Algeria, which possesses a tourist wealth of natural resources, historical, cultural, in addition to the security stability. These constituents represents one of the most important fields of investment in tourism, which is expected to achieve the economic benefits, social, cultural, and environmental, and for the benefit of the community. That's why the tourism industry attracted the attention of the Algerian Country, the Government has taken many procedures to support and encourage this vital industry, especially with important attraction points where issued many laws and decisions that created a whole legislative structure to make tourism investment in Algeria attracting a lot of capitals in order to obtain the greatest return through global tourism. The study aims to encourage tourism investment in the cultural and natural heritage resources in Algeria economically by creating tourist projects, such as investment in accommodation services, hotels, restaurants, parks in addition to promoting tourism-related industries such as handicrafts. A descriptive method has been used for this study, also on the tourist development strategy principles that was adopted by the Algerian Government in sustainable tourism development Act 2003. One of the most important results of the study that the basic infrastructure for the advancement of the development process of the tourist investment is available and this encourages investment and tourism projects in Algeria and this will enhance the contribution of tourism to GDP and in foreign currency.